2-Local superderivations on the deformative super W-algebras Wλs(2, 2). Issue 9 (2nd September 2022) - Abdaoui, Meher
Abstract: The present article is devoted to studying 2-Local superderivations on the deformative super W -algebras W λ s (2, 2). It is proved that all 2-Local superderivations on the deformative super W -algebras W λ s (2, 2) are superderivations.